Predictors of response to pharmacotherapy in children and adolescents with psychiatric disorders: A combined post hoc analysis of four clinical trial data - Takashi Tsujii; Hitoshi Sakurai; Hiroyoshi Takeuchi; Takefumi Suzuki; Masaru Mimura; Hiroyuki Uchida (Wiley, 2022)
Abstract Objective The prediction of response to pharmacotherapy has not been sufficiently explored in children and adolescents with psychiatric disorders, which was addressed in this study. Methods Data from four double‐blind, placebo‐controlled studies (sertraline and fluvoxamine for anxiety disorders, risperidone for autistic disorder, and fluoxetine for major depressive disorder) in children and adolescents funded by the National Institute of Mental Health were used. The response was defined as a score of 1 or 2 on the Clinical Global Impression‐Global Improvement (CGI‐I) at the endpoint. Logistic regression analysis was performed to evaluate associations between response status and the following variables: sex, diagnosis, treatment allocation, and CGI‐Severity of Illness (CGI‐S) score at baseline. Moreover, the presence of early improvement (a score of ≤3 in the CGI‐I) at Week 1 was added to the independent variables in an additional binary logistic regression analysis, using the data from two studies. Results A total of 599 patients were included in the analysis. In the binary logistic regression analysis, active drug use (odds ratio [OR] = 8.64, P < 0.001) and female sex (OR = 1.89, P = 0.002) were significantly associated with treatment response. In the second binary logistic regression, the presence of early improvement in the CGI‐I (OR = 3.47, P = 0.009), as well as active drug use (OR = 15.05, P < 0.001) and female sex (OR = 2.87, P = 0.016), were associated with subsequent responses. Conclusion Allocation to active drugs, female sex, and early improvement may predict treatment response to pharmacotherapy among children and adolescents with psychiatric disorders.